2011
DOI: 10.1186/1755-7682-4-26
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination learning with variable stimulus 'salience'

Abstract: BackgroundIn nature, sensory stimuli are organized in heterogeneous combinations. Salient items from these combinations 'stand-out' from their surroundings and determine what and how we learn. Yet, the relationship between varying stimulus salience and discrimination learning remains unclear.Presentation of the hypothesisA rigorous formulation of the problem of discrimination learning should account for varying salience effects. We hypothesize that structural variations in the environment where the conditioned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The reward history from a S D influences the probability of choosing it again on subsequent trials [ 4 , 10 13 , 20 ]. Because location habits are a common feature of animal behavior [ 4 , 21 ], it is crucial to carefully choose the training sequences of locations for the S D .…”
Section: Resultsmentioning
confidence: 99%
“…The reward history from a S D influences the probability of choosing it again on subsequent trials [ 4 , 10 13 , 20 ]. Because location habits are a common feature of animal behavior [ 4 , 21 ], it is crucial to carefully choose the training sequences of locations for the S D .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it was shown that a single infusion of excitatory amino acid antagonists can increase locomotor activity over 60 min (Wirtshafter et al 1989). Consistently, discriminative learning is thought to depend on various factors including the salience of unconditioned stimuli, salience of conditioned stimuli, and similarity of discriminating stimuli (Trevino et al 2011). In any case, the conditioning effects are consistent with our theoretical view that the incentive motivation enhanced by intra-MR ZK is affective, a process that recruits memory processes to induce conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…In this task, the animals learned to associate that swimming toward a conditioned stimulus (CS + ) and reaching a transparent submerged platform was rewarded with escape from water, whereas swimming toward a non-conditioned stimulus (CS − ) was not. For every trial, we displayed the CS + in a different arm of the pool according to a Gellerman-like schedule (Treviño et al, 2011 ; Herrera and Trevino, 2015 ). Choices were considered as made, once the animals crossed an imaginary line that outlined a decision area with visual access to both CS + and CS − images (Treviño et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…where c 1 , c 2 , n 1 , and n 2 are constants. Also, we defined λ as a sliding logistic function of the net salience, because we assumed that the quality of sensory representation would degrade gradually as salience reached α min , compromising discrimination and learning (Treviño et al, 2011 ):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation